The Analysis of Impoliteness Strategies on Ice Cube's Songs - Ananta Oka Sugawa; Diana Anggraeni; Dini Wulansari (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study analyzes impoliteness strategies, specifically identifying the types and functions of impoliteness strategies contained in the lyrics of rap songs from Ice Cube. The total rap songs used in this study amounted to 10 rap songs. This research uses descriptive qualitative as a research method. There are 53 lines of stanza in lyrics taken and after being identified the data related to the type and function of Jonathan Culpeper's impolite strategy theory. The results of the analysis indicate that most used impoliteness strategy appears in the lyrics of rap songs from Ice Cube is Positive Impoliteness with 24 data. In the lyrics of the song, Ice Cube uses a lot of taboo words, unfamiliar words, and improper identity changes. In addition, the function Affective Impoliteness is the most used in the lyrics with 20 data. In addition, this study also describes the representation of the African-American race described by Ice Cube through the lyrics of the rap song. What can be found is the use of terms that refer to the African-American race, the way that the police treat the African-American race, and also the representation of the injustices that the African-American race gets.